项羽形象与项羽故事 ：诸体文学中的演绎论历代文学中的项羽及其现代意义 = Xiang Yu and Xiang Yu’s stories : the interpretation in each literacy form a study of Xiang Yu’s image in literary works and its modern significance - 蔡詩敏 Chua, Shi Min (2016)
本文以项羽为研究对象，重点论述他在历代文学中的形象，是如何被继承与改造的。由于项羽的形象历来颇为固定，是以本文通过分析经典的项羽故事及其改写，力求发掘有别于一般的项羽形象。在此基础上提炼出的项羽精神与精髓，与现代世人的价值系统本质相同，故项羽历经两千多年，仍能轻易唤起人们的共鸣，使后代念念不忘。This thesis focuses on exploring Xiang Yu’s image in literary writings from past dynasties till today. As Xiang Yu has a rather fixed image, analysing the adaptation and rewriting of Xiang Yu’s classical stories is necessary, to help provide a further disclosure of his other sides. On this foundation, hopefully what holds the true essence in Xiang Yu’s spiritcould be decipher, and in turn explains the long-lastingness of Xiang Yu complex since his time.